Determination of fipronil LD50 for the brazilian bee Melipona scutellaris - Lourenco, Clara T. (2012)
To better understand the sensitivity of the models represented by Apis mellifera L., 1758 in toxicology studies of insecticides to bees, the aim of this study was to determine the LD50 of fipronil by topical application on the stingless bees Melipona scutellaris Latreille, 1811. Foraging bees were collected at the nest entrance and in laboratory anesthetized with CO2 for applying 1.0 mu L of fipronil solution on the pronotum. Each group of treatments was made with thirteen bees divided in three cages, while in the control treatments the bees received only acetone. During the assay, the behavior and the number of dead bees were registered. The results showed that the insecticide fipronil applied topically was harmful to M. scutellaris and for A. mellifera, where the LD50 for 48 hours was 0.41 ng a.i./bee or 4.1 ng a.i./g of bee. Comparing the LDso values here obtained with the stingless bee M. scutellaris and those of A. mellifera in literature, we can conclude that the native bees are more sensitive to fipronil than the allochtonous bee, suggesting that further studies should be accomplished to determine the real hazard of pesticides to natives bees.